Designing the future: youth innovation, informality and transformed VET - Monk, David; Adrupio, Scovia; Muhangi, Sidney; Akite, Irine (Environmental Education Association of Southern Africa (EEASA), 2023)
This article argues that Vocational Education and Training (VET) can be a valuable space to develop the innovation required to deal with the wicked problems of the world; however, radical and rapid transformation in approaches to VET is needed. While we use a case study from Gulu, Uganda, the findings can be applied more broadly. A new approach cannot be taken in isolation from other social circumstances, and desperately needs to include epistemic contributions both in relation to content and approach so that it bolsters and supports the initiatives, designs and dreams of the intended participants, especially women. We argue that epistemic injustice is a major limiting factor for environmental learning and innovation. We share potential opportunities from our research to shift towards a climate and socially conscious social skills ecosystem capable of designing a positive future.
Keywords: Transformative Vocational Education and Training (VET); Social skills ecosystem; Epistemic justice; Environmental sustainability; Intersectionality and VET; SDG-4: Quality education